Evolution Mechanism on Structural Characteristics of Lead-Contaminated Soil in the Solidification/Stabilization Process - Li, Jiang-shan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the use of Solidification/Stabilization (S/S) to treat lead-contaminated soils, which are widely present in China. It reveals the evolutionary mechanism of the structural characteristics of Pb contaminated soil during the S/S process. In addition, the book systematically analyzes laws influencing the S/S process and its internal mechanisms, and develops new models for the strength prediction and Pb leaching prediction of S/S monolith. The results can provide essential theoretical guidance and parameter-related support for the design of Pb-contaminated soil S/S remediation and recycling solutions.
Introduction -- Interfacial Mechanical Effect and Micro-mechanism of Pb-Soil Interaction -- Study on Mechanism of Phosphate-based Cementing Material for S/S of Pb Contaminated Soil -- Evolution on Engineering and Micro structural Characteristic of S/S Treated Pb Contaminated Soil -- Environmental Prediction Model for Leaching Process of S/S treated Pb-contaminated Soil -- Long-term monitoring and analysis evaluation of S/S remediation of Pb-contaminated Soil -- Conclusions and Prospects.
Keywords: Mechanics, Applied; Solids; Environmental engineering; Biotechnology; Bioremediation; Engineering geology; Pollution; Solid Mechanics; Environmental Engineering/Biotechnology.; Geoengineering; Pollution